Polymeric Based Therapeutic Delivery Systems Prepared Using Electrohydrodynamic Processes - Rasekh, M.; Nazari, K.; Arshad, M. S.; Kucuk, I.; Haj-Ahmad, R.; Hussain, A.; Ahmad, Z. (Bentham Science Publ Ltd, 2016)
The development of therapeutic dosage (e.g. pharmaceutical) systems is an ongoing process which, in recent times has incorporated several emerging disciplines and themes at timely intervals. While the concepts surrounding dosage forms have developed and evolved, many polymeric excipients remain as the preferred choice of materials over existing counterparts, serving functions as matrix materials, coatings and providing other specific functional properties (e.g. adhesion, controlled release and mechanical properties). There have been, however, developments in the deployment of synthetic polymeric materials (e.g. polycaprolactone, poly lactic co-glycolic acid) when compared to naturally occurring materials (e.g. lactose, gelatin). Advances in pharmaceutical process technologies have also provided novel engineering platforms to develop a host of exciting structure based materials ranging from the nanometer to the macro scales. Some of these structure enabling technologies include spray drying, super critical processing, microfluidics and even wet chemical methods. More recently electrohydrodynamic (EHDA) engineering methods have emerged as robust technologies offering potential to fabricate a plethora of generic structures (e.g. particles, fibres, bubbles and pre-determined patterns) on a broad scale range. This review focuses on key developments using various EHDA technologies for the pharmaceutical and biomaterial remits when selecting synthetic and/or naturally occurring polymers as pharmaceutical (and therapeutic) excipients. In addition, the underlying EHDA process principles are discussed along with key parameters and variables (both materials and engineering). EHDA technologies are operational at ambient conditions and recent developments have also demonstrated their viability for large scale production. These are promising technologies which have potential in established (e.g. films, dressings and microparticles) and emerging scientific themes (e.g. nanomedicines and tissue engineering).
Keywords: Electrohydrodynamic; fibres; particles; bubbles; printing; drug delivery; encapsulation; natural polymers and synthetic polymers; actives; processing; engineering